Analysis of Cracks on a Fractured Surface of the Vehicle Crankshaft Using the Finite Element Method - ., Husaini; E. Putra, T.; ., Zulfikar (International Journal of Engineering and Technology, 2018)
The purpose of this study is to determine the cause of fracture of a crankshaft. From visual examination, there was a beach mark on the surface, which is common in fatigue failure due to dynamic load. From the chemical composition testing, it was found that the material is classified into alloy steel. Hardness values of the material are based on the Rockwell method, which account the difference between the hardness values on the sides of the edge with the hardness in the middle part. The highest hardness value occurred on the outer edge of the cross section of the crankshaft on the X and Y axes at points 1 and 14, which was 102.2 HRB. A finite element analysis was per- formed to find out the values of stress, strain and deformation that occurred on the component of the crankshaft while operating. From these results, maximum stress and strain occur in the crank pin radius number 1. Finally, it can be concluded that fractures in the crank- shaft occur for several reasons including fatigue failure, material hardness that is not in accordance with the standard, and initial cracks found in the radius of the area crank pin number 1.Â Â